Administration of Creatine Monohydrate® increased the estrogen levels but have no effect on testosterone levels in male albino rats (rattus norvegicus) with moderate physical activity - Ursula Sulistiani; Wimpie Pangkahila; Alex Pangkahila (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2019)
Background: Our laboratory assessment indicated that the Creatine Monohydrate® supplement contains phytoestrogen and phytoprogesteron. This study was aimed to prove that the administration of Creatine Monohydrate® supplement could increase the estrogen levels and decrease testosterone levels in male albino rats (Rattus norvegicus) with moderate physical activity given. Methods: A true experimental with pre-test and post-test randomized control study was conducted using 14 albino male rats. The samples were divided into two groups; the control groups (P0) that received aquadest and moderate physical activity, and treatment group (P1) that received 0.4 mg Creatine Monohydrate® supplement twice a day and moderate physical activity given. Moderate physical activity (swimming) was given five times a week for 14 days. Estrogen and testosterone level were assessed before and after treatment was given. Results: Before the treatment, the estrogen and testosterone levels between P0 group and P1 group were comparable. Post-test results showed a significant different in estrogen levels between the P0 and P1 group (23.17±2.86 and 27.82±3.06 ng/ml respectively; p<0.05) as well as testosterone levels (18.15±2.95 and 21.69±2.14 ng/ml respectively; p<0.05) after 14 days of treatment. A paired analysis showed an elevating of estrogen levels but no effect on testosterone levels in P1 group that treated with Creatine Monohydrate® Conclusion: This study indicated that the administration of Creatine Monohydrate® increased the estrogen levels but have no effect on testosterone levels in male albino rats (Rattus norvegicus) with moderate physical activity.